Cancer-associated fibroblasts: dual roles from senescence sentinels to death regulators and new dimensions in therapy - Ruan, Guixiang; Wang, Xiang; Ou, Huiyi; Guo, Duancheng (Frontiers in Immunology, 2025)
Cancer-associated fibroblasts (CAFs) are critical components of the tumor microenvironment (TME), playing a pivotal role in tumor initiation, progression, and therapeutic resistance. This review explores the dual roles of CAFs in regulating tumor cell senescence and cell death, elucidating their mechanisms in inducing cellular senescence, shaping an immunosuppressive milieu, and modulating cell death pathways. CAFs promote tumor progression by secreting pro-inflammatory factors and extracellular matrix (ECM) components, while also contributing to metabolic reprogramming, immune evasion, and therapy resistance, thereby influencing anti-cancer treatment efficacy. Studies indicate that the heterogeneity and plasticity of CAFs determine their distinct functions across various tumor types. Consequently, precision-targeted therapeutic strategies against CAFs, including the elimination of senescent CAFs, inhibition of the senescence-associated secretory phenotype (SASP), and disruption of CAF-mediated cell death evasion mechanisms, have emerged as promising directions in cancer research. This review provides a comprehensive analysis of CAFs functions and their potential as therapeutic targets, offering valuable insights into the development of novel anti-cancer strategies.